2010
DOI: 10.1055/s-0030-1267923
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Preoperative Features of Pleuropulmonary Blastomas (PPB) from Congenital Cystic Adenomatoid Malformations (CCAM): a Retrospective, Age-Matched Study

Abstract: PPB patients continue to represent a diagnostic challenge. Asymptomatic and predominantly cystic PPB remain indistinguishable from CCAM preoperatively. A high index of suspicion for PPB must be considered in any child presenting with cystic lung lesions beyond early infancy, particularly in a child with poor weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 12 publications
2
34
2
Order By: Relevance
“…Both infants recovered fully. It has been reported that PPB may be indistinguishable from CCAM radiologically in a retrospective case-matched series 39. However, this series relied on small numbers and described only infants who presented postnatally and were symptomatic in 9/10 of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Both infants recovered fully. It has been reported that PPB may be indistinguishable from CCAM radiologically in a retrospective case-matched series 39. However, this series relied on small numbers and described only infants who presented postnatally and were symptomatic in 9/10 of cases.…”
Section: Discussionmentioning
confidence: 99%
“…PPB presents a diagnostic challenge since it is difficult to distinguish from benign lung lesions either prenatally or in early childhood [2,3,4]. Thus, the diagnosis is most often only made by histology.…”
Section: Discussionmentioning
confidence: 99%
“…A solid type III tumor is more pathognomonic but typically presents in older children [2]. A strong family history of neoplasia can prompt suspicion for PPB but is positive in only 40% of cases [1,3]. …”
Section: Discussionmentioning
confidence: 99%
“…A pathological classification system was proposed by Stocker et al and later expanded to include types 0 to 4 [4–6]. However, there is often discrepancy between the type of CPAM based on imaging and the ultimate pathological diagnosis after resection [7–9]. …”
mentioning
confidence: 99%